2017
DOI: 10.1038/s41598-017-05552-1
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors and the Risk for Fracture at Specific Sites: Data Mining of the FDA Adverse Event Reporting System

Abstract: Proton pump inhibitors (PPIs) are widely used to treat gastric acid-related disorders. Concerns have been raised about potential fracture risk, especially at the hip, spine and wrist. However, fracture risk at other bone sites has not been as well studied. We investigated the association between PPIs and specific fracture sites using an aggregated knowledge-enhanced database, the Food and Drug Administration Adverse Event Reporting System Data Mining Set (AERS-DM). Proportional reporting ratio (PRR) was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 52 publications
0
18
0
4
Order By: Relevance
“…A positive, albeit modest, association between PPIs and OP was reported in animal [ 262 , 263 , 264 ] and numerous of human studies. Many studies and meta-analyses suggested that acid inhibitors, especially the PPIs, moderately increase risk of fractures, particularly in older adults (who are already at higher fracture risk); the risk increases with longer durations of PPI use, often only in the presence of at least one other RF for OP such as older age, female gender and a higher comorbidity score [ 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 ]. Moreover, use of PPIs may also increase risk of falls [ 291 , 292 , 293 ].…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%
“…A positive, albeit modest, association between PPIs and OP was reported in animal [ 262 , 263 , 264 ] and numerous of human studies. Many studies and meta-analyses suggested that acid inhibitors, especially the PPIs, moderately increase risk of fractures, particularly in older adults (who are already at higher fracture risk); the risk increases with longer durations of PPI use, often only in the presence of at least one other RF for OP such as older age, female gender and a higher comorbidity score [ 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 ]. Moreover, use of PPIs may also increase risk of falls [ 291 , 292 , 293 ].…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%
“…22 This has been acknowledged by Federal Drug Administration, which has labeled PPIs as being known to increase the likelihood of a fracture. 10 There is also growing evidence of an association between prolonged PPI use and increased risk of spine fractures. 16,17 This growing body of evidence relating PPIs and fractures suggest that these medications have an adverse effect on bone quality and may affect stability with instrumentation in elective spine fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Wyniki badań z ostatnich lat prezentują jednak wyraźną zależność między stosowaniem IPP a występowaniem rzadkich, lecz ważnych klinicznie, skutków ubocznych długotrwałej terapii. W licznych publikacjach pojawiły się doniesienia o wpływie IPP między innymi na rozwój zakażenia Clostridium difficile, otępienia u osób starszych czy na istotne zwiększenie podatności kości na złamania [11][12][13]. Istnieją również podejrzenia dotyczące wpływu IPP na powstawanie niedoboru witaminy B 12 [14], co wynikać może z obniżenia kwaśności soku żołądkowego.…”
Section: Działania Niepożądane Inhibitorów Pompy Protonowejunclassified